Planning Concept of Lalebbata: Combining Heritage, Policy and Participation - Liza Utami Marzaman; Zulham Hafid; Amiruddin Akbar Fisu; Nurhijrah Nurhijrah (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2021)
Palopo City is a member of the Indonesian Heritage City Network (JKPI) and has been directed by the government as a Heritage City. Lalebbata is an important space in the history of Palopo City. In this area, the pulse of the economy, socio-culture and religiosity of the Palopo people begins. The intertwining of these three aspects is symbolized by the existence of the market – as the center of crowds, the Kedatuan Palace of Luwu and the Old Mosque of Palopo City. Lalebata as one of the historical areas needs efforts to be structured as an effort to revive activities in this area as well as as an effort to protect, including controlling the development of the area so as not to lose its historical identity. The Regional Regulation of the City of Palopo on Cultural Heritage mandates that the spatial pattern of the Cultural Conservation Area is stipulated in the Batupasi Sub-District. The management plan for this cultural heritage area includes the revitalization of cultural heritage, as well as the preservation and maintenance of historical buildings as well as being directed as a Trade and Service Allocation Area, particularly as a shopping center and public open space. This paper aims to produce a planning concept and arrangement of the Lalebbata Area in Batupasi as a Center of Heritage as well as a public space in Palopo City. The method used is a participatory approach to the residents living around the site, to explore potential and problems, as well as to review policies related to planning and arrangement that will be carried out. The result of this paper is the area planning concept by dividing the area into several functions such as commercial space, public and pedestrian space, green area/parks/sclupture, plaza, exhibition space and museum.